Microsoft Sentinel skills - Gordon, Adam (Packt Publishing, 2024)
Discover the power of Microsoft Sentinel with our specialized course for IT and security professionals. Begin with a deep dive into Sentinel's architecture, learning the prerequisites for a successful deployment to maximize its potential. Explore essential topics such as roles, permissions, and cost management, preparing you to implement and manage Sentinel effectively. Gain hands-on experience with the deployment process, starting from the onboarding steps. Navigate the platform and familiarize yourself with its features to build a solid foundation for advanced usage, enhancing your confidence and competence in utilizing Sentinel for security operations. The final section of the course delves into advanced configurations and practical applications. Learn to deploy out-of-the-box content, connect threat intelligence platforms, create custom analytics rules, and enable UEBA. Master the skills needed to optimize Sentinel for your specific needs, culminating with lessons on configuring Fusion rules for multistage attack detection. Protect your organization from sophisticated threats with Microsoft Sentinel.
Online resource; title from title details screen (O'Reilly, viewed August 5, 2024)
Keywords: Microsoft Azure (Computing platform); Cloud computing -- Security measures; Microsoft Azure (Plateforme informatique); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet